Both industrial and small-scale aviculture need development - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
seminar in Hamelin, West Germany, organized by the German Agricultural Society (DLG) in cooperation with CTA, from June 20-24. 1987